Development of Microsoft Access-Based Electronic Records Management Information System (E-Archives) in Postgraduate - Trirahayu, Yohana Endang; Sumartiningsih, Sri; Laksito, Wendro (Educational Management, 2022)
application design, testing and implementation. The results of this research are application program design, and applications that have been designed can be used as an alternative to solving problems in Postgraduate. The use of a design system based on Microsoft Access is expected to help the office administration section to be able to manage records effectively and efficiently by using electronic media in managing records, the benefits of speed and convenience will be obtained.